Differential equations - Mateo, Rolando A; Bandoy, Lourdes G.;Fainsan, Delia S.;Lazaro, Rosario S.;Mendoza, Rodolfo V.;Nobles, Bernadeth G.;Sirug, Winston S.;Sictchon, Daubrey C. (Cavite : M.R.T.T.C. Publication, 2005)
It is fervent hope and ardent desire of the authors that this book would be very instrumental in enhancing and optimizing the knowledge of the students in the field of mathematics.
Chapter 1. Fundamental concepts -- Chapter 2. Solution of a differential equation -- Chapter 3. Solution of a first order differential equation -- Chapter 4. Solution of a first order differential equation -- Chapter 5. Solution of a first order differential equation -- Chapter 6. Solution of a first order differential equation -- Chapter 7. Determination of integrating factor -- Chapter 8. Application of differential equation -- Chapter 9. Homogeneous linear differential equations -- Chapter 10. Non-homogeneous linear differential equations -- Chapter 11. Laplace transformations -- Chapter 12. Inverse laplace transforms.
Includes bibliographical references.
Keywords: DIFFERENTIAL EQUATIONS -- MATHEMATICS